Standby power trolleys to mitigate load shedding using a lease or lease-to-buy business model - Du Toit, Johannes Jacobus (University of the Witwatersrand, Johannesburg, 2024)
The business venture envisions a brighter future for South Africa by providing reliable and affordable power solutions, with a focus on empowering small businesses. Exploratory research, leveraging a qualitative research methodology, was conducted and a public demand for a solution was established. The unique approach involves a power trolley lease and lease-to-buy model, allowing customers to test backup power solutions before committing to a specific solution. To support its vision, the business developed key capabilities such as customer management, product development, distribution, and marketing. An analysis indicates the potential for competitive advantage once the organization is established. In the macro environmental analysis, the business identifies a market opportunity based on persistent power challenges in South Africa and economic constraints, creating a demand for cost-effective backup power solutions. The industry analysis suggests an attractive industry with low buyer power and limited competitive rivalry. The ventures positioning statement emphasizes a comprehensive service experience, offering innovative backup power products (power trolleys) with connected customer support. The venture’s operational plan is driven by a supply chain strategy focused on responsiveness to meet the urgent backup power needs of small businesses, aligning with the connected marketing strategy. The venture plans to focus its marketing and sales strategy on digital channels like Google advertisements and Facebook advertisements, specifically targeting the Gauteng region to minimize costs associated with physical advertising. The business adopts a differentiation pricing strategy, emphasizing quality service, given the lack of direct competitors. The founder plans to bootstrap the venture to retain control and minimize costs. The venture’s preliminary financial forecasts project positive net profit, balance sheet growth, and positive cash flow after the second year of operation. It was concluded through methodical research that a solution to power outages in the South African context would provide a strong basis for a business venture. The business analysis conducted showed the optimal strategy and process to exploit the opportunity identified.
A research project submitted in partial fulfillment of the requirements for the degree of Master’s in Business Administration. Johannesburg, 2024 to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg 2024
Keywords: Backup power; BVP; Business Venture Proposal; Power Trolley; Inverter; Lease; Lease-to-buy; UCTD; SDG-8: Decent work and economic growth